Multiple sequential free flap reconstructions of the head and neck: a single-center experience - Moratin, Julius; Horn, Dominik; Heinemann, Maleen; Semmelmayer, Karl; Mrosek, Jan Bernd; Ristow, Oliver; Engel, Michael; Freudlsperger, Christian; Freier, Kolja; Hoffmann, Jürgen (Plastic and reconstructive surgery, 2021)
Background: - Free flap reconstruction is the standard of care in extensive defects of the head and neck area, and although most patients may be treated sufficiently with one flap, recurrence of a malignant tumor or failure of a previous reconstruction may make the use of a second (or more) flap necessary. The aim of this study was to evaluate the indications and success rates of multiple consecutive reconstructive procedures in a large cohort of patients. - Methods: - Nine hundred ninety-six free flap reconstructions were retrospectively analyzed and cases of sequential reconstructions in the same patient were identified. Indications, success rates, perioperative procedures, and frequently used flaps were evaluated. - Results: - Two hundred twenty cases of sequential microvascular reconstructions were identified, ranging from two to six flaps per patient. The overall flap success rate was 89.1 percent. A history of diabetes was identified as a risk factor for flap failure (p = 0.029). There was no association of flap loss with the number of reconstructive procedures per patient. - Conclusions: - The use of several free flaps in the same patient is a feasible option for patients suffering from recurrent tumors or to improve quality of life by a secondary reconstruction. A salvage free flap transfer to replace a lost transplant exhibits good success rates. - CLINICAL QUESTION/LEVEL OF EVIDENCE: - Therapeutic, IV.
Gesehen am 03.12.2021